The Role of Saltmarsh Plants in Iron Age and Roman Salt Production in the Thames Estuary, UK - Edward Biddulph (EXARC, 2016)
Analysis of plant remains and soils collected during excavations of the Iron Age and Roman Period salt production site at Stanford Wharf Nature Reserve on the coast of Essex have shown that saltmarsh plants and adhering sediments had been used as fuel to evaporate brine and crystallise the sea salt. It was further suggested in report of the fieldwork (Biddulph et al. 2012) that the ash of the fuel was itself a useful by-product, being steeped in the brine to create a stronger solution. The idea was not tested at the time that the report was being prepared, but in this paper, I report on experiments designed to test that hypothesis. The results show that burnt samphire (representative of saltmarsh plants), when steeped in seawater, enhances the salinity of the water, resulting in a brine that is more concentrated than one created from seawater alone. What is more, given an equal volume of brine, the brine and ash solution yields a higher amount of salt than does the seawater-only brine. The experiments support the suggestion made in the Stanford Wharf report, and have implications for the understanding of coastal salt production in the Iron Age and Roman period.